(untitled) (diségno, 2024)
Since the 15th century, the model was used for the representation of design proposals to be submitted to the client, presented at competitions, and exhibited to the citizens to inform them of future urban transformations. We therefore find, alongside models of entire buildings, models related to individual portions object of the competition, such as domes, architectural details, façades. Representation by model allowed clients to express themselves after a critical-comparative reading facilitated by a greater familiarity with reality. The article contextualizes in the historical period and analyses examples of design models of architectural façades, a particular typology defined in the title as ‘two-dimensional’ since the possibility of relating the representation of the façade to the internal or otherwise overall spatiality of the building, which normally characterizes the model, is denied. However, they are certainly classifiable as models, both for the materials used and for the three-dimensionality of the detailed elements and the consequent effects of light and shadow that can be perceived, as well as for the modality of use that is not constrained to a single point of view as occurs in the elevation drawings, and therefore allows showing the corner solution. The analysis is carried out through the presentation of emblematic examples and their comparison with the corresponding drawings.